Using publicly available social and spatial data to evaluate progress on REDD+ social safeguards in Indonesia - Jagger, P.; Rana, P. (Elsevier, 2017)
Countries are grappling with how to monitor and evaluate the social impacts of reducing emissions from deforestation and forest degradation (REDD+) at national and sub-national scales as they develop REDD+ safeguard information systems (SIS). Given limited resources for social safeguard measuring, reporting and verification (MRV), and the fact that REDD+ is a performance based mechanism requiring monitoring over the medium to long-run, there is a need to develop SIS that are low cost, rigorous, and sustainable over time. Of critical importance are approaches that adequately operationalize social safeguards, provide opportunities for ongoing MRV, and are feasible in terms of within country human and financial capital. In this paper we provide an illustration of how publicly available social and spatial data can be used for the quantitative evaluation of the social impacts of early REDD+ activities using the example of Kalimantan, Indonesia.